How Does Child Disadvantage Change with Age? An Analysis of Australian Children. Issue 4 (2nd October 2018) - Mishra, Ankita; Ray, Ranjan; Risse, Leonora
Abstract: This paper applies a dynamic multidimensional measure of disadvantage to examine how the nature and extent of disadvantage experienced by a child can vary throughout their childhood. We use two longitudinal datasets to track a cohort of Australian children from around 4 to at least 10 years of age, comparing the experiences of Indigenous children to the broader Australian child population. Our analysis confirms that Indigenous children not only experience worse rates of disadvantage than the rest of the Australian child population at all ages, but that this gap widens further as children grow older. For all Australian children, the highest rates of disadvantage are detected in "bullying" and "body weight, " with rates of unhealthy body weight worsening with age. The empirical findings of this study can inform age-targeted policy design; while the methodological contributions have relevance for other countries aiming to target the well-being of disadvantaged socioeconomic groups.